Impact of sleep quality on disease progression in early-stage amyotrophic lateral sclerosis - Gan Zhang; Gan Zhang; Gan Zhang; Yong Chen; Yong Chen; Yong Chen; Lu Tang; Lu Tang; Lu Tang; Linna Bai; Hui Zhang; Hong Liu; et al. (Frontiers in Neurology)
Non-motor symptoms are clinical manifestations of amyotrophic lateral sclerosis (ALS). However, few studies have examined these symptoms in patients with early-stage ALS. We conducted a cross-sectional study to explore non-motor symptoms in 69 patients with ALS within 18 months of disease onset. The Pittsburgh Sleep Quality Index (PSQI), the Epworth Sleepiness Scale (ESS), and the Hospital Anxiety and Depression Scale (HADS) were used to evaluate sleep quality, daytime sleepiness, and anxiety and depression, respectively. Differences in the abovementioned non-motor symptoms between ALS patients and age-/sex-matched caregivers were examined, and correlations between these symptoms and the clinical features of ALS were analyzed. Compared to caregivers, ALS patients were more likely to report poor sleep [odds ratio (OR) and 95% confidence interval (95% CI) = 2.664, 1.276–5.560; p = 0.009] and excessive daytime sleepiness (EDS) [OR and 95% CI = 5.135, 1.640–16.072; p = 0.005]. The PSQI scores in ALS patients correlated significantly with the disease progression rate [ΔFS = (48-score on the Amyotrophic Lateral Sclerosis Functional Rating Scale-Revised, ALSFRS-R)/disease duration] [β(95% CI) = 2.867 (0.397, 5.336), p = 0.024] and plasma neurofilament light chain (NfL) levels [β (95% CI) = 0.041 (0.012, 0.070), p = 0.008). Our results revealed that the patients with early-stage ALS experienced poor sleep quality and daytime sleepiness and suggested that low sleep quality may be related to more rapid disease progression. Confounders were not obvious in the early stage of ALS, and our results suggested that these symptoms may be related to more severe and extensive pathological changes in the central nervous system.